An exploration of the nature of relationship that exists between the surviving HIV positive spouses and their significant others at Gaths Mine in Masvingo Province. - Mugwamba, Chiedza (Midlands State University, 2018)
The relationship that exists between a surviving HIV positive spouse and their significant other has an impact on the well being and nature of life style the surviving spouses will led. A supportive relationship empowers surviving spouses to lead a positive and full life surrounded by loved ones. The study sought to explore of the nature of relationship that exists between the surviving HIV positive spouses and their significant others at Gaths Mine in Masvingo Province The surviving spouse’s positive status seems to have an effect on the nature of relationships that exist between them and their significant others especially in young men and women. Reports have increased from spouses experiencing unfair treatment and injustice in their home setting soon after losing their loved one. An interpretivist phenomenological research approach under qualitative approach was employed which allowed the researcher to dig deep on the experiences of the HIV positive surviving spouses. The target population for this research were HIV positive widows and widowers who lost their loved ones to the pandemic and utilised the outpatient services at the Gates Mine hospital. The sample was drawn through homogeneous purposive sampling .Sixteen participants who were both male and female were selected. A semi structured interview guide was the tool of choice in carrying out the study. Findings from the study uncovered that during their married life, knowledge about their HIV status came about as a result of an event such as illness or a partner testing positive for HIV. There was diversity in the experience of the spouses that lived in sero-positive and sero-discordant relationships during their married life. Intimacy and Disclosure to significant others and children proved to be one of the challenges faced. After the death of a spouse, findings indicated that Blame and shame were amongst the most prominent emotions that were felt. Perceptions of stigma and anticipated discrimination affected how surviving spouses related with other at the funeral as well as long after the death of a loved one. The most prominent explanation of the findings from the study illustrate that social support is an important aspect to surviving spouses especially those with children and living through difficulty and financial trouble. Based on all this evidence the researcher concluded that both partners needed to elevate communication on their problems, integrating their significant other into knowing their statuses. This approach would allow them to stand by each other before death interfered with their lives. This level of interaction allowed the significant others to acknowledge and accept their conditions simultaneously reducing chances of blame, guilt and shame if one of the partners passed away.